My video coach - a phenomenographic interpretation of athlete perceptions of coaching through a live video feed - Bennett, B. C. (Qualitative Research in Sport, Exercise and Health, 2021)
Despite the numerous reported benefits of implementing technology-enhanced learning (TEL) strategies in sport coaching, and advancements in the `user-friendliness` of technologies available to human movement educators, learner perceptions of such pedagogies are yet to be fully understood. In an effort to address this, the current article employed a phenomenographic methodology to present the variation of conceptions, or understandings, of athletes involved in a `Video Coach (VC)` project - whereby a coach and athletes connected regularly via video calling technology during a preparation phase for high performance competition. The current article builds on a procedural account of the VC project by exploring the ways in which participants` discerned the various elements of the encounter. Here, phenomenography, an emerging research methodology in the sport coaching literature, offered the advantage of providing different understandings to a contemporary coaching approach. Upon interpreting the individual ways in which the phenomenon (the VC encounter) was experienced, the outcome space demonstrates the interrelatedness of athletes` perceptions by showing that it was considered a necessary, albeit an `authoritative` observation tool, beneficial in absence of alternative arrangements or conventional (read: face-to-face) coaching approaches. In this sense, the VC project was a `needs-must` approach for participants, and was valued as such. This study provides a starting point for future research, where coaches and researchers could explore the benefits and drawbacks of a VC in a range of other human movement contexts according to athlete perception(s).